Alienated Wisdom : Enquiry into Jewish Philosophy and Scepticism - Veltri, Giuseppe (Studies and texts in scepticism, 2018)
The present study addresses problems of an epistemological nature which hinge on the question of how to define Jewish thought. It will take its start in an ancient question, that of the relationship between Jewish culture, Greek philosophy, and then Greco-Roman (and Christian) thought in connection with the query into the history and genealogy of wisdom and knowledge. Our journey into the history of the denomination 'Jewish philosophy' will include a leg that will lead us to certain declarations of political, moral, and scientific principles, and then on to the birth of what is called philosophia perennis or, in Christian circles, prisca theologia. Our subject of inquiry will thus be the birth of the concept of Jewish philosophy, Jewish theology and Jewish philosophy of religion. A special emphasis will fall on the topic treated in the last part of this study: Jewish scepticism, a theme that involves a philosophical attitude founded on dialectical "enquiry", as the etymology of the Greek word skepsis properly means